Heterogeneity of cellular inflammatory responses in ageing white matter and relationship to Alzheimer's and small vessel disease pathologies. (15th February 2021) - Waller, Rachel; Narramore, Ruth; Simpson, Julie E.; Heath, Paul R.; Verma, Nikita; Tinsley, Megan; Barnes, Jordan R.; Haris, Hanna T.; Henderson, Frances E.; Matthews, Fiona E.; Richardson, Connor D.; Brayne, Carol; et al.
Abstract: White matter lesions (WML) are common in the ageing brain, often arising in a field effect of diffuse white matter abnormality. Although WML are associated with cerebral small vessel disease (SVD) and Alzheimer's disease (AD), their cause and pathogenesis remain unclear. The current study tested the hypothesis that different patterns of neuroinflammation are associated with SVD compared to AD neuropathology by assessing the immunoreactive profile of the microglial (CD68, IBA1 and MHC‐II) and astrocyte (GFAP) markers in ageing parietal white matter (PARWM) obtained from the Cognitive Function and Ageing Study (CFAS), an ageing population‐representative neuropathology cohort. Glial responses varied extensively across the PARWM with microglial markers significantly higher in the subventricular region compared to either the middle‐zone (CD68 p  = 0.028, IBA1 p  < 0.001, MHC‐II p  < 0.001) or subcortical region (CD68 p  = 0.002, IBA1 p  < 0.001, MHC‐II p  < 0.001). Clasmatodendritic (CD) GFAP + astrocytes significantly increased from the subcortical to the subventricular region ( p  < 0.001), whilst GFAP + stellate astrocytes significantly decreased ( p  < 0.001). Cellular reactions could be grouped into two distinct patterns: an immune response associated with MHC‐II/IBA1 expression and CD astrocytes; and a more innate response characterised by CD68 expression associated with WML. White matter neuroinflammation showed weak relationships to the measures of SVD, but not to the measures of AD neuropathology. In conclusion, glial responses vary extensively across the PARWM with diverse patterns of white matter neuroinflammation. Although these findings support a role for vascular factors in the pathogenesis of age‐related white matter neuroinflammation, additional factors other than SVD and AD pathology may drive this. Understanding the heterogeneity in white matter neuroinflammation will be important for the therapeutic targeting of age‐associated white matter damage. Abstract : Although white matter lesions (WML) are associated with cerebral small vessel disease (SVD) and Alzheimer's disease (AD), their cause and pathogenesis remain unclear. Glial responses vary extensively across the parietal white matter (PARWM) with diverse patterns of white matter neuroinflammation. Understanding the heterogeneity in white matter neuroinflammation will be important for the therapeutic targeting of age‐associated white matter damage.